Testimonios de violencia y destrucción de imágenes en época de Lactancio - Tomás García, Jorge (Romanitas - Revista de Estudos Grecolatinos, 2016)
The understanding of the changes in attitudes that Christians took to the religious imagery in the course of the centuries is essential to understand the pagan, Christian and Late Antique art. However, the resistance to the represented image was particularly strong in part by the central role that images and statues in general, were at the thought of the Greco-Roman pagan religion. Objects that were attacked, destroyed, mutilated or removed were decorative and symbolic, narrative and didactic images devices. The works of Lactantius serve as a mirror of historical trends in III-IV centuries, culminating moment in which there was a shift in the attitude towards the pagan images.
Keywords: Imagen; Lactantius; Iconoclasm; Violence; Late Antiquity